Wanprestasi Jual Beli Tanah Di Bawah Tangan Yang Berakibat Pada Proses Balik Nama (Studi Putusan Nomor 347/Pdt.G/2022/PN SBY) - Putri, Nindy Budiartie Permani (Peneliti.net, 2024)
Default or breach of promise is an event where one party does not adequately complete its obligations in the engagement. For example, the legal case in Decision Number 347/Pdt.G/2022/PN SBY is a case of default in the sale and purchase of land, which was originally carried out with an agreement under the hand. In this case, the seller did not fulfill his promise to be present to sign the Deed of Sale and Purchase in front of a Notary / PPAT which resulted in the Buyer having difficulties in processing the transfer of land rights. The problem discussed is how legal protection for land buyers who will transfer the name of the land rights if the seller defaults in the sale and purchase of land under the hand and what factors are considered by the judge in making a decision on the case of default in the sale and purchase of land under the hand which results in the process of transferring the name. The author uses a normative research method that aims to collect written legal sources by reviewing previous laws and publications. With the results of the discussion, namely that the form of legal protection against buyers of land rights due to buying and selling under the hand can be done repressive legal protection efforts, namely legal protection that leads to efforts to resolve disputes. And in Decision Number 347/Pdt.G/2022/PN SBY the Judge decided the case on the basis of Article 125 paragraph (1) HIR, that the Panel of Judges granted the Plaintiff's claim by verstek.